Antecedents of IT-Business Alignment Factors in Influencing Sustainable Competitive Advantage - Al-Majali, Dmaithan A. (2011)
More extensive studies on the causal chain between Information Technology (IT) investments and firm performance have been encouraged by scholars. However, the results of empirical studies have been inconclusive. This is partly due to the exclusion of IT - business strategic alignment (known as strategic alignment). In particular, scholars have continuously called for research to address the antecedent factors that lead to the alignment. As a result, this study has successfully developed a causal model illustrating the relationships between strategic alignment antecedents, strategic alignment and sustainable competitive advantage. Specifically, this study has looked into the impact of IT-business strategic alignment antecedents in terms of leadership between business and IT managers, structures and processes between IT plans and business plans and examined IT managerial resources between business and IT managers, service qualities, values and beliefs, and IT implementation success on IT business strategic alignment in terms of alignment gaps. Finally, the impact of IT-business strategic alignment is also tested for its impact on sustainable competitive advantage. In order to explore the above research relationships, this study has utilized the positivism paradigm. Under this method, quantitative data was collected. More specifically, this study has tested the research model by conducting 172 survey questionnaires with public shareholding firms in Jordan. The results obtained from the structural equation modeling (SEM) technique and interviews have offered very valuable insights into the research questions. The results of the main survey questionnaire show strong evidence for the impact of the following variables: leadership, service quality, value and belief, IT managerial resources and IT implementation success, on IT – business strategic alignment. Conversely, SEM has failed to support the link between structure and process on IT business alignment. In addition, the results show strong evidence for the impact of the following: leadership, IT managerial resource and IT implementation success on sustainable competitive advantage. However, SEM failed to support the link between service quality, value and belief, and structure and process on sustainable competitive advantage. Furthermore, the results from the main survey questionnaire show strong evidence for the impact of IT – business strategic alignment on sustainable competitive advantage. Moreover, the results of the main survey questionnaire through the SEM show strong evidence for the mediating effect of strategic alignment on the relationships between value and belief, service quality and sustainable competitive advantage. This study has provided a detailed roadmap that researchers and practitioners can use in order to understand the resources required, and to realize the potential values of their IT investments. Future research is clearly needed to reveal better insights into the nature of these relationships.